2021
DOI: 10.3390/ani11113008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Eucommia ulmoides Extract Alleviates the Effect of Cold Stress on Chick Growth Performance, Antioxidant and Immune Ability

Abstract: This study aimed to investigate the protective value of Eucommia ulmoides extract (EUE) on chicks under cold stress. A total of 21 compounds were identified in EUE using mass spectrometry (LC-MS). Ninety chicks were divided into a control group (CS) fed a basal diet and an experimental group supplemented with EUE, exposed to 10 ± 1 °C for 8 h per day. Results showed, compared with the CS group, the body weights (BW) (p < 0.01) and average daily gains ADG (p < 0.05) of the EUE group were increased through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…According to Hu et al (2021), adding Eucommia ulmoides water extract to the basal diets of cold-stress chicks improves ABW, ADG, ADFI and decreases feed-to-gain ratios. Dietary supplementation of Eucommia ulmoides leaves reduces the serum concentration of TC in laying ducks (Feng et al, 2023), and plasma TG and TC levels in laying hens (Peng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Hu et al (2021), adding Eucommia ulmoides water extract to the basal diets of cold-stress chicks improves ABW, ADG, ADFI and decreases feed-to-gain ratios. Dietary supplementation of Eucommia ulmoides leaves reduces the serum concentration of TC in laying ducks (Feng et al, 2023), and plasma TG and TC levels in laying hens (Peng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One recent study reported that the dietary supplementation of 250 mg/kg of Eucommia ulmoides leaf extracts obviously increased the ADG of broilers in the early stage (1–21 days), and reduced the feed conversion ratio in the whole period (Yan et al, 2022). According to Hu et al (2021), adding Eucommia ulmoides water extract to the basal diets of cold‐stress chicks improves ABW, ADG, ADFI and decreases feed‐to‐gain ratios. Dietary supplementation of Eucommia ulmoides leaves reduces the serum concentration of TC in laying ducks (Feng et al, 2023), and plasma TG and TC levels in laying hens (Peng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations